Peningkatan Kemampuan Pemecahan Masalahdan Hasil Belajar Matematika MelaluiStrategi Kooperatif Tipe TPS (Think Pair Share)Pada Siswa Kelas VII Semester GenapDi SMP Negeri 1 Grogol Tahun Ajaran 2016/2017 - Sejani, Amin Sri (2016)
Amin Sri Sejani / A 410120028. Peningkatan Kemampuan Pemecahan Masalah dan Hasil Belajar Matematika melalui Strategi Kooperatif Tipe TPS (Think Pair Share) pada Siswa Kelas VII Semester Genap di SMP Negeri 1 Grogol Tahun Ajaran 2016/2017. Skripsi. Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Surakarta. Februari, 2016. The purpose of this research is to describe the improvement of problem solving ability and mathematics study achievement by applying cooperative strategy think pair share. This research is a Classroom Action Research (CAR) collaborative. The subject of the research that receive the action is grade VII G SMP Negeri 1 Grogol are 32 students. The data collection techniques are observation, field notes, test, documentation and interview. The technique of data analysis is interactive analysis method. The data validity uses triangulation source and technique. Result of the research is showing the improvement of problem solving ability and mathematical study achievement in compilation. It can be seen from the increasing student's problem solving ability and student's mathematics study achievement indicator namely; 1) understand the problem, students can identify the elements that are known, asked, and the adequacy of the elements that required before action as much as 37.50% increase to 81.25 %; 2) Plan the settlement, construct a mathematical model, and implement strategies for solving as much as 31.25% increase to 62.50%; 3) complete the planning and draw conclusions as much as 22.40% increase to 56.25; students who scored passing grade ≥ 75 before the action as much as 31.25% increase to 71.87%. The conclusion of this research is that the adoption of cooperative strategies Think Pair Share (TPS) can improve problem solving ability and mathematics study achievement class VII G SMP Negeri 1 Grogol academic year 2016/2017.